Adolescents and nutrition information-seeking: the role of the Internet - Larsen, Jessica Nicole, author; Martey, Rosa Mikeal, advisor; Anderson, Jennifer, committee member; Seel, Peter Benjamin, committee member (Colorado State University. Libraries, 2010)
The purpose of this thesis is to examine the ways adolescents find and make sense of nutrition information, giving special attention to the role of the Internet in that process. Adolescents' behaviors and opinions relevant to finding nutrition information were investigated using Kuhlthau’s (1993) iterative model of information-seeking as a theoretical foundation. Since many skills are required to search, engage with, and use online information sources and information, the information-seeking process was investigated in relationship to an applied context of eHealth literacy (Norman & Skinner, 2006a), referred to as eNutrition literacy. From six in-depth interviews and a brief paper-and-pencil questionnaire with seventy-nine adolescents aged 12-16 two trends emerged: 1) these adolescents were primarily presented with and fulfilled nutrition information needs in formal settings such as school and 2) these adolescents used the Internet to fulfill primarily personal needs. Therefore, a conflict existed between the ways they used the Internet and the ways they were presented with a nutrition information-seeking task. Nutrition-specific information literacy, media literacy, health literacy, and scientific literacy, created challenges in stages of the information-seeking process as well. Fundamentally, this affected their overall engagement with online nutrition information and their ability to receive the maximum benefits from the online information-seeking process.
Department Head: Greg Luft.